Is allergy an autoimmune process? (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2024)
Allergy diseases continue to increase as demonstrated by the multiple epidemiological studies published. The most important allergic symptoms are respiratory (rhinitis, sinusitis, asthma), followed by cutaneous and systemic symptoms. More and more diagnostic and therapeutic methods developed, aimed on the one hand at identifying the responsible allergens (Skin test, specific challenges, specific antibodies determinations, molecular analysis…But what we still do not know is why a person who is informed by his mother of all the allergens with which she had contact, and therefore should tolerate them, at a certain moment ih his life, begins to not recognize them and consider the pathogens, and your immune system triggers an aggressive response against itself, what is known as “hypersensitivity”, which ultimately has a similar definition to “autoimmunity”: damage to your own tissues.One type of hypersensitivity is autoimmune diseases, which affect 5% of the population and include well-known syndromes such as rheumatoid arthritis, psoriasis and lupus.Why does something as harmless and natural as pollen trigger such an aggressive response in the lungs of an atopic patient who had previously inhaled them without problems? Why does a previously tolerated food or drug cause anaphylaxis or why do you no longer tolerate the pet that has lived with you for so many years? Why do autoimmune diseases occur? To try to answer this enigma, it is necessary to be clear about some concepts and mechanisms of the immune response that we are going to summarize.
Keywords: Autoimmunity, allergy, allergens, antibodies